Film deposition and consolidation during thin glove coagulant dipping. Issue 22 (11th January 2017) - Groves, Robert; Routh, Alexander F.
ABSTRACT: In this article, we examine the rate of film build‐up and the evolution of polymer volume fraction in coagulant dipped films. The results are for nitrile and natural rubber compounds. We describe a model for the build‐up of a latex film that coagulates onto a former as a wet gel and consolidates by a wet sintering process. We achieve this by applying diffusion and reaction kinetics for the coagulant transporting from a former into the latex bath. Wet sintering, the underlying mechanism for serum exudation from the wet gel, is modelled for a consolidating aggregate of latex particles. The parameters used in the models are either measured in separate experiments or are available from the literature. We compare the model predictions with the experimental results. The first, rapid, stage of film build‐up is modelled successfully by simple diffusion of the coagulant cations. At longer dwell times, it is found that the reaction between coagulant and surfactant is the primary mechanism for the rate reduction. The rate of consolidation of the wet gel could be modelled reasonably well using a previously developed equation for latex film formation. The rate was chiefly dependent on the stress relaxation modulus of the polymer. © 2017 Wiley Periodicals, Inc. J. Polym. Sci., Part B: Polym. Phys.2017, 55, 1633–1648 Abstract : Thin elastomeric gloves are currently the most important products made by the coagulant dipping process, finding use in the medical, scientific, and food industries as well as in many other areas. A model is presented that predicts the thickness of a latex film during glove dipping. The usual assumption of diffusional growth is shown to be accurate for early times, but a subsequent departure is ascribed to reaction between the coagulant and surfactant.